Preventing Neurodegeneration by Controlling Oxidative Stress: The Role of OXR1 - Volkert, Michael R.; Crowley, David J. (Frontiers in Neuroscience, 2020)
Parkinson’s disease, diabetic retinopathy, hyperoxia induced retinopathy, and neuronal damage resulting from ischemia are among the notable neurodegenerative diseases in which oxidative stress occurs shortly before the onset of neurodegeneration. A shared feature of these diseases is the depletion of OXR1 (oxidation resistance 1) gene products shortly before the onset of neurodegeneration. In animal models of these diseases, restoration of OXR1 has been shown to reduce or eliminate the deleterious effects of oxidative stress induced cell death, delay the onset of symptoms, and reduce overall severity. Moreover, increasing OXR1 expression in cells further increases oxidative stress resistance and delays onset of disease while showing no detectable side effects. Thus, restoring or increasing OXR1 function shows promise as a therapeutic for multiple neurodegenerative diseases. This review examines the role of OXR1 in oxidative stress resistance and its impact on neurodegenerative diseases. We describe the potential of OXR1 as a therapeutic in light of our current understanding of its function at the cellular and molecular level and propose a possible cascade of molecular events linked to OXR1’s regulatory functions.